The Development of Exposition Paragraph Writing Ability of Grade 10-12 Students of MAN 2 Model Medan - Sibarani, Berlin; Hafiz Aziz, Muhammad (Journal of Language, Literature and Teaching, 2019)
This research was aimed at describing the extent to which the grade 10,11, and 12 students acquire the paragraph development of exposition paragraph writing and to describe the process of acquiring the paragraph development. The development of exposition paragraph was analyzed by following the theory of Knapp and Watkins (2009:152) that consists of text structure and lexico-grammar. The text structure is used to see the logical flow of ideas from the beginning until the end of the paragraph, while the lexico-grammar refers to the wordings to form meaning. To achieve the objectives of this study, this research was conducted by using descriptive qualitative design which relied on words to describe the phenomena. The data was analyzed following Miles et.al’ s model. The research finding showed that first, the students from grade 10,11, and 12 had not acquired the development of exposition paragraph writing since they only put thesis statement, argument, but there was no conclusion. Second, the development of exposition paragraph could not be explained since the subjects did not relate the thesis statement to the argument and they did not provide conclusion. However, the development can be seen through the greater use of lexico-grammar from grade 10, 11 until 12.